The characteristics of Coconut Fiber-Based Composites And Sugar Fiber-Based Composites - Asfarizal (Jurnal Teknik Mesin, 2016)
Composites made from natural plant fibers that are environmentally friendly is now more attractive, lighter weight, the number of abundant, renewable, competitive prices has encouraged the use of a broad field of engineering, building interiors and clothing. The characteristics of each fiber is highly variable and influenced by the maturity of fiber materials, processing into fiber, perlakauan after so fibers and fiber treatment. Known properties of fiber can help choose the method that is right and good to be applied in the manufacturing process of composite. Pretreatment, composition and matrix settings, select the type of adhesive is a method that is widely used to obtain physical and mechanical properties superior but physical properties and mechanical produced highly variable and not consistent.